A Rapid and Practical Method for Deprotection of 1,1-Diacetates Catalyzed by Zirconium Sulfate Tetrahydrate-Silica Gel (Journal of Sciences, Islamic Republic of Iran)
A simple and efficient procedure for converting a variety of 1,1-diacetates into the corresponding aldehydes was developed. The methodology has been done with zirconium sulfate tetrahydrate-silica gel as catalyst. The temperature plays an important role in these reactions. The phenolic acetate function can selectively be deprotected into phenol.